Accounting Doctoral Program Demographics - Baldwin,Amelia A; Brown,Carol; Trinkle,Brad S (Advances in Accounting Education: Teaching and Curriculum Innovations, 2010)
Accounting doctoral programs are often evaluated and ranked based on various measures of publishing productivity, both of graduates and of faculty. While publishing is very important in academia, the choice to attend a PhD program is complex. In addition, the variables that can give insight into a PhD program and its graduates are far more diverse than simply the research productivity of a program's faculty and graduates. The purpose of this investigation is to describe and analyze U.S. doctoral accounting programs using a variety of demographic data about the programs and their most recent graduates. This includes addressing these broad research questions: What are the demographic characteristics of the graduates of each program, including gender, and minority status? What are the demographics descriptors of these graduates' current employment situations?
Keywords: Accounting; Dean's Office

Accounting Doctoral Program Demographics - Baldwin,Amelia A; Brown,Carol; Trinkle,Brad S (Advances in Accounting Education: Teaching and Curriculum Innovations, 2010)
Accounting doctoral programs are often evaluated and ranked based on various measures of publishing productivity, both of graduates and of faculty. While publishing is very important in academia, the choice to attend a PhD program is complex. In addition, the variables that can give insight into a PhD program and its graduates are far more diverse than simply the research productivity of a program's faculty and graduates. The purpose of this investigation is to describe and analyze U.S. doctoral accounting programs using a variety of demographic data about the programs and their most recent graduates. This includes addressing these broad research questions: What are the demographic characteristics of the graduates of each program, including gender, and minority status? What are the demographics descriptors of these graduates' current employment situations?
Keywords: Accounting; Dean's Office

The Geography of Accounting Doctoral Placement - Brown,Carol; Baldwin,Amelia A (American Accounting Association Annual Meeting, 2010)
Keywords: Accounting; Dean's Office

Accounting, Diversity, and the AAA Diversity Section - Brown,Carol; Baldwin,Amelia A (Diversity Section of the American Accounting Association Mid-Year Meeting, 2009)
Keywords: Accounting; Dean's Office

Accounting Doctoral Program Demographics - Brown,Carol; Baldwin,Amelia A; Trinkle,Brad S (2009 Annual Meeting of the American Accounting Association, 2009)
Keywords: Accounting; Dean's Office

Minority Accounting PhDs: Origins and Destinations - Brown,Carol; Baldwin,Amelia A (Diversity Section of the American Accounting Association Mid-Year Meeting, 2009)
Keywords: Accounting; Dean's Office

Accounting Doctoral Program Demographics - Baldwin,Amelia A; Brown,Carol; Trinkle,Brad S (American Accounting Association Diversity Section Mid-Year Meeting, 2008)
Keywords: Accounting; Dean's Office

An Analysis of the Accounting Doctoral Industry: Observations and Unanswered Questions - Brown,Carol; Baldwin,Amelia A (American Accounting Association Diversity Section Mid-Year Meeting, 2008)
Keywords: Accounting; Dean's Office

Minority PhDs in Accounting: Distribution and Trends - Brown,Carol; Baldwin,Amelia A; Trinkle,Brad S (American Accounting Association Annual Meeting, 2008)
Keywords: Accounting; Dean's Office

PhDs in Accounting: Gender Distribution and Trends - Brown,Carol; Trinkle,Brad S; Baldwin,Amelia A (American Accounting Association Annual Meeting, 2008)
Keywords: Accounting; Dean's Office

Opportunities for AI Development in the Accounting Domain: The Case for Auditing - Baldwin,Amelia A; Brown,Carol; Trinkle,Brad S (Intelligent Systems in Accounting, Finance and Management, 2006)
This paper reviews the nature of accounting and auditing problems and the need for application of Artificial Intelligence (AI) technologies to the discipline. The discussion includes current accounting issues for which new AI development should be fruitful particularly auditing and assurance.
Keywords: Accounting; Dean's Office

Opportunities for AI Development in the Accounting Domain: The Case for Auditing - Brown,Carol; Baldwin,Amelia A; Trinkle,Brad (Fifteenth Annual Research Workshop on: Artificial Intelligence and Emerging Technologies in Accounting, Auditing and Tax, 2006)
Keywords: Accounting; Dean's Office

Research Streams in Continuous Audit: A Review and Analysis of the Existing Literature - Brown,Carol; Wong,Jeff; Baldwin,Amelia A (Twelfth World Continuous Auditing and Reporting Symposium, 2006)
Keywords: Accounting; Dean's Office

Research Streams in Continuous Audit: A Review and Analysis of the Existing Literature - Brown,Carol; Wong,Jeff; Baldwin,Amelia A (Fifteenth Annual Research Workshop on: Artificial Intelligence and Emerging Technologies in Accounting, Auditing and Tax, 2006)
Keywords: Accounting; Dean's Office

Artificial Intelligence in Accounting: The Case for Auditing - Brown,Carol; Baldwin,Amelia A; Trinkle,Brad S (The Twenty-fifth SGAI International Conference on Innovative Techniques and Applications of Artificial Intelligence, Workshop on AI in Accounting, Finance and Management, 2005)
Keywords: Accounting; Dean's Office

Research Streams in Continuous Audit: A Review and Analysis of the Existing Literature - Brown,Carol; Wong,Jeff; Baldwin,Amelia A (The 10th World Continuous Auditing Symposium, 2005)
Keywords: Accounting; Dean's Office

XBRL: An Impacts Framework and Research Challenge - Brown,Carol; Baldwin,Amelia A; Trinkle,Brad (Thirteenth Annual Research Workshop on: Artificial Intelligence and Emerging Technologies in Accounting, Auditing and Tax, 2004)
Keywords: Accounting; Dean's Office